PEMANFAATAN FANPAGE FACEEBOOK: PENJAHIT KEBAYA DAN SALON DI DESA SIOPAT SOSOR KABUPATEN SAMOSIR - Pasaribu, Romindo M; Simanjuntak, Juara; Matondang, Vinsensius; Tampubolon, Frans Yolanda; Purba, Juliansen (LPPM Institut Pendidikan Nusantara Global, 2024)
The kebaya sewing service industry and beauty salons are industries that are always in demand by Indonesian people both in cities and in regions. Kebaya is a traditional Indonesian dress. Every religious event and custom almost always uses kebaya cloth. In using kebaya cloth at every event, Indonesian women always make up themselves so that the kebaya cloth used looks more beautiful and beautiful when worn. Therefore, the kebaya cloth sewing industry and beauty salons are one of the service industries that are in great demand by the public in starting a business. The purpose of this community service activity is so that people who start kebaya sewing and beauty salon businesses can reach a wider market by utilizing social media accounts such as Facebook in promoting their business. Facebook social media accounts can be turned into business accounts by adding a fanpage or business page feature. Facebook fanpage is a special page like a blog that contains various kinds of content according to the wishes of its users. The results of this activity are kebaya sewing and beauty salon business actors who have changed their personal Facebook account to a business Facebook account by adding a fan page feature. So that business actors in kebaya sewing and beauty salons can expand their market share through promotions on social media.